Eccentric hamstring strength profile and limb asymmetry in sub-elite female taekwondo athletes: Implications for injury prevention - Christina Septya Dewi; Pudjijuniarto Pudjijuniarto; Awang Firmansyah; Roy Januardi Irawan (Sport, Exercise, and Injury, 2025)
Background: Taekwondo is a physical contact sport requiring quick reactions and explosive movements such as kicking, which depend heavily on hamstring muscle strength to maintain performance and reduce injury risk. Objectives: This study aims to profile the eccentric hamstring strength and asymmetry in sub-elite female taekwondo athletes in East Java. Methods: This was a quantitative descriptive study with a cross-sectional approach. A total of 22 female athletes with regional competition experience and no lower limb injuries were selected using purposive sampling. Data were collected using the NordBord by Vald Performance, a reliable tool for measuring eccentric hamstring strength and asymmetry. Descriptive statistics analyzed the mean, standard deviation, minimum, maximum, and strength percentage relative to normative values. Results: The athletes had an average age of 18.86±2.05 years, body mass of 57.45±8.90 kg, height of 160.68±6.72 cm, and BMI of24.33 ±2.51. Eccentric hamstring strength was 89.6% in the left leg, 85% in the right leg, and 87.2% overall, indicating the need for improvement. Conclusions: The eccentric hamstring strength of both legs needs to be increased by approximately 12.8% while maintaining the current low asymmetry level to support muscle balance. Targeted hamstring strengthening exercises are recommended to enhance performance and reduce injury risk. This study is limited to female athletes; further research should include broader populations and variables.